The Difference between Bacterial Growth in Humidifier and Non Humidifier at the Patient Who Got Oxygen Therapy - Abu Bakar; Krisna Yetti; Hanny Handiyani (Universitas Airlangga, 2008)
Introduction: Humidifier is a device for delivering oxygen to the patients. Before using it, the humidifier tube should fill with sterile water. There was a recent study that administering oxygen less than five liter per minutes, the tube was not load with the sterile water. This research aim was to describe the difference between bacterial growth in the humidifier and non humidifier at the patient who got oxygen therapy. Method: The design was the analytic survey with purposive sampling method. The samples were 24 patients. They were divided into two groups. Group one, consisted of 12 patients with humidifier and the others with non humidifier. The instrument was culture equipments diagnostic test and observation guidance. The hypothesis was there was no difference bacterial growth existence in humidifier and non humidifier at the patient who got oxygen therapy. Result: The results showed that there was no significance difference of bacterial growth at time of zero hour (p=0.131). Meanwhile, there was significance different of bacterial growth at time of 12 hour (p=0.046), and time of 24 hour (p=0.046). There was also significance different between bacterial growth in humidifier and non humidifier at the patient who got oxygen therapy (p=0.010). Discussion : The conclusion is a non humidifier device could prevent bacterial and reduce nosocomial infection. It was recommended that hospital should use non humidifier and the humidifier had to disinfect and change the water every 12 hours.